Pengamatan Cuaca Lokal secara Multi Node dengan Internet of Things dan Django Framework - Saputra, Muh Aris; Utomo, Wahyu Cahyo; Setiawan, Ahmad Bagus; Ramadhanu, Ilham Khefi (Universitas Boyolali, 2024)
Weather is one of the challenges that humans must experience in their activities. Like the MSMEs of sand crackers in Kediri Regency. This MSME uses sunlight as a means of drying products. What often becomes a problem is unpredictable weather conditions which reduce productivity and quality. Therefore, a real-time local weather observation system is needed to anticipate sudden weather changes. In this research, an IoT-based local weather condition measurement tool will be connected to a system built using the Django framework. This system and tools were tested for eight days. So it was concluded that the system was successfully built with data collection accuracy of 96.31%. Measurements are carried out every 5 minutes or a time frame of 5 minutes. In addition, this system supports observations in several places at once. This multiple node concept is used to detect local weather changes in the surrounding area. So it is not concentrated in the MSME area.